Behavioral Problems at Age 11 Years After Prenatal and Postnatal Exposure to Acetaminophen: Parent-Reported and Self-Reported Outcomes. Issue 6 (24th November 2020) - Inoue, Kosuke; Ritz, Beate; Ernst, Andreas; Tseng, Wan-Ling; Yuan, Yuying; Meng, Qi; Ramlau-Hansen, Cecilia Høst; Strandberg-Larsen, Katrine; Arah, Onyebuchi A; Obel, Carsten; Li, Jiong; Olsen, Jørn; et al.
Abstract: Several studies have reported associations between prenatal acetaminophen exposure and behavioral outcomes in young children. We aimed to evaluate the associations of prenatal and postnatal exposures to acetaminophen with behavioral problems in children at age 11 years, using behavioral measures reported by parents and children. We studied 40, 934 mother-child pairs from the Danish National Birth Cohort enrolled during 1996–2002. Parent-reported and child-reported Strengths and Difficulties Questionnaire (SDQ) responses were collected during the 11-year follow-up. We estimated risk ratios for behavioral problems including total difficulties as well as internalizing or externalizing behaviors following prenatal (during pregnancy) or postnatal (within the first 18 months after birth) acetaminophen exposure. Parent-reported and child-reported SDQ scores were moderately correlated; higher for externalizing ( r  = 0.59) than internalizing ( r  = 0.49) behaviors. Prenatal acetaminophen exposure was associated with 10%–40% higher risks for total difficulties and internalizing and externalizing problems based on parent- or child-reported SDQ, with the association being stronger for greater cumulative weeks of acetaminophen use. Postnatal exposure was associated with 16%–19% higher risks for parent-reported internalizing behaviors, but the associations were weak or null for child-reported scores except for prosocial behavior. Our study corroborates published associations between prenatal exposures to acetaminophen and behavioral problems and extends the literature to early adolescence.